Steelwork design guide to BS5950-1:2000 - Md. Tahir, Mahmood (Penerbit UTM, 2010)
This book takes into account the revisions of the code of practice of steel structures by enhancing the previous BS 5950:1990 with the updated code of BS 5950:2000 Part 1. The specification or code changes have affected the design of the members in steel structures. Most of the text and worked examples relate to the most commonly encountered design situations have been addressed in this book. Therefore, the procedures for design at the cross–sectional member and frame level for various situations are explained in great details. This book needs to be read together with BS 5950:2000 Part 1 so that the details of the explanations on the use of code can be understood clearly. Although this book has been prepared to integrate the use of BS 5950:2000 Part 1, the basic principle of analysis and design described in this book can also be applied to other code of practice such as Euro–code 3.